2007
DOI: 10.1007/s00464-007-9539-7
|View full text |Cite
|
Sign up to set email alerts
|

Gastric banding: Conversion to sleeve, bypass, or DS

Abstract: A review of conversions of gastric banding for obesity to Roux-en-Y gastric bypass, gastric sleeve, or duodenal switch attempts to determine which revisional procedure best enhances weight loss. Indications for these conversions are multiple and include hardware problems, motility problems, and miscellaneous like inadequate weight loss. Analysis of band conversions to band of 193 patients, and bands to gastric bypass in 214 patients reveals better weight loss with the latter strategy. Smaller cohorts of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 30 publications
2
52
1
2
Order By: Relevance
“…Failed or complicated bands are normally rebanded, or band is removed and the patient is revised to SG or bypass. 4,14 We performed SG (in two patients) and VBG (in two patients) as revision procedures. Mini-pouch gastric bypass was performed in one patient because of patient preference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failed or complicated bands are normally rebanded, or band is removed and the patient is revised to SG or bypass. 4,14 We performed SG (in two patients) and VBG (in two patients) as revision procedures. Mini-pouch gastric bypass was performed in one patient because of patient preference.…”
Section: Discussionmentioning
confidence: 99%
“…Several technical options are offered as an alternative to failed VBG: Revision VBG, conversion to Roux-en-Y gastric bypass, to gastric banding and recently to SG. 8,14,[19][20][21][22][23] Studies have shown that SG is safe and effective in achieving adequate weight loss in most patients. 24,25 We performed Roux-en-Y gastric bypass in one and SG in two patients with failed VBG.…”
Section: Discussionmentioning
confidence: 99%
“…AGB is relatively simple to perform, reversible, and safe [2]. However, the AGB can cause numerous complications, including slippage, erosion, migration, and esophageal dilatation due to gastric outlet obstruction or stenosis [3][4][5]. In addition, approximately 14.3-50% of these patients require revision or conversion surgeries [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the weight loss resulting from gastric banding is less compared to a combined restrictive and malabsorptive procedure like gastric bypass [3]. Some patients with insufficient weight loss after gastric banding undergo conversion to gastric bypass, which often results in superior weight loss [4][5][6].…”
Section: Introductionmentioning
confidence: 99%